Professional Characteristics of Primary School Teachers in Ilia Prefecture and Job Satisfaction - Μπαντούνα Μαρία; Ζωγόπουλος Κωνσταντίνος (Education Sciences, 2021)
Teachers' level of satisfaction with their work is a determinant factor for the learning process, the quality of education and teachers’ well-being. Many factors both intrinsic and extrinsic to work affect the level of their job satisfaction. The purpose of this research study, which is part of a larger study, is to investigate the relationship between professional characteristics (job position, total years of service, job status and level of education) of primary school teachers in the prefecture of Ilia and their level of satisfaction with the intrinsic and extrinsic factors of the work. The research was quantitative. It was carried out using the Job Satisfaction Scale, JSS questionnaire by Warr, Cook and Wall (1979). The sample of the study was 269 primary school teachers. The results of the research showed that the professional characteristics of the teachers have a significant influence on their perceptions of their satisfaction with the intrinsic and extrinsic factors of the work.